Fluorescence Caused by Pseudomonas in the Mucus of Anguispira Kochi (Pfeiffer) - John M. Baum; Hugh C. Rawls (Hello World!, 1972)
Fluorescence underultraviolet light has been reported to occur in the mucus of Helix aspersa (Muller (Turchini, 1926; Fischer and Saddy, 1949) and in the epiphragms of certain other snails (Fischer, 1956). The mucus from living specimens of certain endodontid species and the alcohol used to preserve these and other species of the family have been found to emit a blue fluorescence when exposed to ultraviolet light (Rawls and Yates, 1971). The same kind of fluorescence has been found to occur in one polygyrid species (Rawls and Baum, 1971).